Analisis kesulitan siswa dalam pemecahan soal cerita sistem persamaan linear dua variabel berdasarkan tahapan polya - Arsandy, Qory Septiani; Siregar, Anisa Rahmadani; Sinuhaji, Ribka Dameria; Ambarita, Zefanya Tabita; Sinaga, Victory Rajani; Siregar, Budi Halomoan (Papanda Publisher, 2025)
Mathematics is one of the subjects that plays an important role in training students' critical thinking and problem-solving skills. However, in practice, many students experience difficulties, especially when faced with story problems that require the ability to understand the context and translate it into a mathematical model. This study aims to analyze students' difficulties in solving word problems on the subject of Two-Variable Linear Equation Systems (SPLDV) based on Polya's problem-solving stages. This study uses a qualitative descriptive approach with 26 ninth-grade students from SMP Negeri 27 Medan as subjects. The research instrument was a written test on SPLDV story problems and was analyzed using Polya's stages, namely understanding the problem, devising a plan, implementing the plan, and checking the results. The results showed that students experienced difficulties at almost every stage. At the stage of understanding the problem, some students failed to identify important information and determine the variables correctly. In the planning stage, many students had difficulty converting the story problems into a system of linear equations. In the execution stage, errors mainly occurred in calculation operations and the application of the elimination and substitution methods. Meanwhile, in the checking stage, most students were unable to relate the solution to the context of the problem and rarely verified their answers. These findings confirm that students' difficulties are systematic, whereby failure at one stage has an impact on the next stage. Therefore, teachers need to emphasize problem-based learning by providing systematic exercises, accustoming students to verification, and training mathematical representation skills so that students are able to minimize errors in solving SPLDV story problems.